Development of nonlinear energy-based method (NEM) controller for 3 DOF helicopter - , Pharmayeni; Akmeliawati, Rini; Legowo, Ari (2011)
In this paper, this design was a Nonlinear Energy-based Control Method (NEM) controller for a Three degree-of-freedom (3 DOF) Helicopter developed by Quanser. It is a control design technique that exploits the energy state of a system to achieve stabilization and/or tracking. There are four stages to design NEM controller, which are: energy-based modeling of helicopter dynamics using Euler-Lagrange formalism; design of the NEM controller based on passivity principle and Lyapunov stability idea; tuning the controller gain(s) to satisfy the design criteria and robustness analysis.